Eksistensi Nilai Kerakyatan Dalam Demokrasi Indonesia - Kania Nova Ramadhani; Yakobus Ndona (International Forum of Researchers and Lecturers, 2024)
This research aims to find out how the existence of populist values in democracy in Indonesia and to understand the fact that Indonesian democracy is based on populist values embodied in the 4th precept of Pancasila. The 4th precept of Pancasila reads “Democracy led by wisdom in deliberation/representation” and contains populist values that underlie democracy in Indonesia. This research uses qualitative methods with literature studies, namely data collection techniques by examining books, journals, and other literary studies. The results of this study show that the existence of populist values in Indonesian democracy is reflected in the principles governing people's participation in decision-making and government behavior towards the people. This shows that Indonesian democracy is based on populist values that require the state to guarantee the participation of the people democratically through their representatives without discrimination.